Histopathological changes after deep anterior lamellar keratoplasty using the 'big-bubble technique' - Braun, Joachim M.; Hofmann-Rummelt, Carmen; Schlötzer-Schrehardt, Ursula; Kruse, Friedrich; Cursiefen, Claus (Acta Ophthalmologica, 2013)
Purpose: During deep anterior lamellar keratoplasty (DALK), endothelium and Descemet's membrane are separated from the corneal stroma by intrastromal air injection ('big-bubble technique'). The aim of our study is to analyse histopathological changes in host corneal tissue caused by air insufflation in patients with keratoconus, their variability in 10 patients and their possible clinical implication. Methods: The excised anterior corneal lamellae of 10 patients with keratoconus having undergone DALK using the 'big-bubble technique' were analysed by light and transmission electron microscopy as well as immunohistochemistry. In addition, intrastromal air accumulations were quantified morphometrically. Results: Intrastromal air was detected in all examined excised lamellae (8% of stromal volume), but with large variability (SD 8.8). It was detected preferentially in the inner layer of the corneal stroma and represented there up to 39% of the stromal volume. In addition, the air was predominantly located at one periphery of the excised lamellae. Intrastromal air bubbles were larger in the inner than in the superficial stromal layer and characterized by round shape and a CD68-negative collagenous 'pseudocapsule'. We detected no air-injection-induced alterations in Bowman's layer and epithelium. Conclusion: Our results show that 'big-bubble DALK' causes significant intrastromal air accumulations in the cornea. Pathologists should be conscious of this phenomenon and the high topographic variability. Intrastromal air in the recipient rim may be accompanied by a decrease in mechanical stability and could contribute to postoperative suture loosening.
EVALuna2:21044